Henrik Ibsen : the critical heritage - Egan, Michael, 1941- (Critical heritage series., 1997)
Henrik Ibsen (1828-1906). Norwegian dramatist, generally acknowledged as the founder of modern prose drama. Writings include: A Doll's House, Ghosts, Rosmersholm. Volume covers period 1872-1906.